The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/978-3-319-32189-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Drug Resistance in Bacteria

Abstract: Resistance to antibiotics is an important and timely problem of contemporary medicine. Rapid evolution of resistant bacteria calls for new preventive measures to slow down this process, and a longer-term progress cannot be achieved without a good understanding of the mechanisms through which drug resistance is acquired and spreads in microbial populations. Here, we discuss recent experimental and theoretical advances in our knowledge how the dynamics of microbial populations affects the evolution of antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“… A proposed scheme of workflow illustrating the use of (A) live imaging technologies to visualize and track the growth and evolution of probiotic bacteria in real-time (Baym et al, 2016), (B,C) advanced molecular tools for the broad coverage and high resolution system level detection and gene expression analysis (Marondedze et al, 2014) and (D) powerful computational approaches for the formation of predictive models simulating the behavior of probiotic bacteria based on laboratory data (Waclaw, 2016), for the assessment of the risk of antibiotic resistance contributed by commercial probiotic strains and their long-term consumption to human health. This integrative approach should be applied in studies that consider the different compositions of the gut microflora such as the presence of a consortia of probiotic strains and pathogens as well as a gradient of antibiotic pressures, and their growth and colonization dynamics in response to various spatial and temporal factors.…”
Section: Assessing the Risk Of Antibiotic Resistance In Probiotics Ofmentioning
confidence: 99%
See 1 more Smart Citation
“… A proposed scheme of workflow illustrating the use of (A) live imaging technologies to visualize and track the growth and evolution of probiotic bacteria in real-time (Baym et al, 2016), (B,C) advanced molecular tools for the broad coverage and high resolution system level detection and gene expression analysis (Marondedze et al, 2014) and (D) powerful computational approaches for the formation of predictive models simulating the behavior of probiotic bacteria based on laboratory data (Waclaw, 2016), for the assessment of the risk of antibiotic resistance contributed by commercial probiotic strains and their long-term consumption to human health. This integrative approach should be applied in studies that consider the different compositions of the gut microflora such as the presence of a consortia of probiotic strains and pathogens as well as a gradient of antibiotic pressures, and their growth and colonization dynamics in response to various spatial and temporal factors.…”
Section: Assessing the Risk Of Antibiotic Resistance In Probiotics Ofmentioning
confidence: 99%
“…For instance, computational models revealed that bacteria may switch to an alternative phenotype [e.g., consuming a different food source (Solopova et al, 2014)] that is less sensitive to a new and unfavorable environmental condition, can afford bacteria time to develop compensatory mutations that offset the effect of the deleterious mutation and regain fitness (Greulich et al, 2012; Waclaw, 2016). The use of mathematical models to simulate how phenotypic switching can provide a larger pool of bacteria to evolve genetic resistance to antibiotics has been previously reviewed (Levin and Rozen, 2006).…”
Section: Assessing the Risk Of Antibiotic Resistance In Probiotics Ofmentioning
confidence: 99%
“…We further use the model to recommend future strategies for prevention of this process. 15 One recent study has further looked at the effect of diffusion-based drug gradients on the effective outcome of population diversity and heterogeneity [8]. This heterogeneity is evident in the biological literature but is yet to be explained by existing mathematical models.…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…For half a century, antibiotics derived from microorganisms have become the leading drugs in different clinical fields due to their distinct structures and excellent activities [2,3]. However, the emerging of drug-resistant bacteria and drug-resistant tumors has prompted people to search for new drugs and novel mechanisms of action [4,5]. More recently, the marine environment is considered as an abundant microbial resource due to its complex ecological environment and relatively harsh living conditions [6,7], which implies there are enormous unexplored secondary metabolites and their biosynthetic gene clusters to be discovered and characterized.…”
Section: Introductionmentioning
confidence: 99%